2030 Agenda and sustainable business models in tourism: A bibliometric analysis. (February 2021) - Rosato, Pier Felice; Caputo, Andrea; Valente, Donatella; Pizzi, Simone
Highlights: An increasing number of tourism companies adopt sustainable strategies. The SDGs represent a new challenge for tourism enterprises. Academics have started to discuss about the enabling role covered by tourism firms. Bibliometric analysis underlines the exigence to develop further studies on SDGs. Abstract: Starting in 2015, 169 states launched a series of initiatives aimed at pursuing achievement of the 2030 Agenda. In particular, one of the main sector interested by 2030 Agenda is represented by the Tourism sector. The centrality of Tourism enterprises is related to the considerable impacts on the landscapes in which they operate. On the point, academics and policy makers have started to discuss about the difficult for Tourism enterprises to adopt business model based on sustainable paradigms such as the circular economy. According to this evidence, this paper aims to analyze the scientific debate that has characterized the first 5 years after the introduction of the 2030 Agenda. Bibliometric analysis has been conducted on 101 articles about the relationship between SDGs and Tourism published during the period 2015–2019. The analysis reveals the existence of three independent clusters of research regarding the impacts on society (Red Cluster), business models (Blue Cluster) and policy implications (Green Cluster). An interpretative framework to evaluate the strategies adopted by tourism enterprises to contribute to the SDGs is then developed and discussed.